A Large Amazonian Peatland Carbon Sink Was Eliminated by Photoinhibition of Photosynthesis and Amplified Ecosystem Respiration - Jeffrey D. Wood; D. Tyler Roman; Timothy J. Griffis; Hinsby Cadillo‐Quiroz; Dennis DelCastillo; Lizardo Fachin; Erik Lilleskov; Randall K. Kolka; Jhon Rengifo; Craig Wayson (Geophysical Research Letters)
Abstract The fate of tropical peatland carbon cycling under environmental change is highly uncertain. We found that a palm swamp peatland in the Peruvian Amazon that was a strong annual sink for 2 years switched to carbon neutral in the absence of a major anthropogenic disturbance. We attributed the change in carbon sink strength to (a) photoinhibition of canopy photosynthesis when skies were clearer and thus solar irradiance higher and (b) increased ecosystem respiration when the water table position was below the peat surface, and heterotrophic respiration was amplified. These mechanisms were not, however, synchronous in time. The importance of photoinhibition as a driver of changes in peatland carbon budgets is a novel finding, and an understudied mechanism of canopy photosynthetic impairment. Shifts in climate that increase periods with sustained high solar irradiance and/or low water table are thus likely to amplify interannual variability in the carbon sink strength.